2023
DOI: 10.3390/en16031199
|View full text |Cite
|
Sign up to set email alerts
|

The Photometric Test Distance in Luminance Measurement of Light-Emitting Diodes in Road Lighting

Abstract: Over the last few years, light-emitting diodes have completely dominated the lighting field. In road lighting, high-power LEDs have replaced traditional light sources. That is why various technical aspects of LEDs have been researched extensively worldwide. However, little research has been conducted in the area of luminance measurement. This paper reviews the methods for measuring the luminance of high-power LEDs. Particular attention is paid to the influence of the measurement distance on the measurement res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…The measurements were intended to demonstrate the constancy or variability of the results obtained for different measurement distances. The analysis of the obtained results would allow the measurements to be compared with those obtained in other studies that concerned high-luminance LEDs [63].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The measurements were intended to demonstrate the constancy or variability of the results obtained for different measurement distances. The analysis of the obtained results would allow the measurements to be compared with those obtained in other studies that concerned high-luminance LEDs [63].…”
Section: Methodsmentioning
confidence: 99%
“…For example, using the ILMD laboratory meter when measuring high-luminance LEDs, the reference image for LED1 occupied 56,640 px, and for LED3 it occupied 149,600 px. In relation to these reference images, the measured images covering about 6000 px for LED1 and about 50,000 px for LED3 ensure the measurement accuracy of 99% [63]. It all depends on the output size of the image and the uniformity of the luminance distribution on a given image.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Studies on the photometric impact of replacing the original light source are limited (Abdullah et al, 2021). Recent studies regarding LED measurement have shown that LED has different characteristics than conventional luminaires and may require different measurement approaches for correct evaluation (Czyżewski, 2023).…”
Section: Introductionmentioning
confidence: 99%